-x-8=-4x+1

Simple and best practice solution for -x-8=-4x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-8=-4x+1 equation:



-x-8=-4x+1
We move all terms to the left:
-x-8-(-4x+1)=0
We add all the numbers together, and all the variables
-1x-(-4x+1)-8=0
We get rid of parentheses
-1x+4x-1-8=0
We add all the numbers together, and all the variables
3x-9=0
We move all terms containing x to the left, all other terms to the right
3x=9
x=9/3
x=3

See similar equations:

| -2(m-4)=-12 | | -2(v-10)=8 | | -156-x=42-10x | | 9t-t=16 | | -8x+3=4x+9 | | 7k+8+7k=-8+10k | | 2.5w-5=1.5w+10 | | 17x+12=54-4 | | 11-3x=9-2x | | 3x-54=11x+66 | | 3x+x-3x=30 | | 5=(9-c)/3 | | y=17-14 | | 4(s+1)-3=13 | | 217-y=258 | | 135=125(343+x)/(379.4) | | -11x-201=x+87 | | 3x+x-3x=30 | | 20-9x=65 | | 7k+8+7k=-88+10k | | 23x6=(20x3)+(3x6) | | p=2(35/6+42/3) | | 96=84-12e | | 2x+5/x=50 | | 12-5=9c+22c | | 12a+10=7 | | 3(-2x-10)=-78 | | -2x-15=-3x+11 | | 1.5x-12.6x=8.4+2.5x | | 42=x+0.20/0.1429(6-x)/0.1429 | | 2(4m+3)=22 | | 3x(2+1)=(3x2)+(3x1) |

Equations solver categories